Ambulatory Patient Groups: Impact on the Service Structure and Providers' Behaviour. Issue 2 (December 2014) - Raulinajtys-Grzybek, Monika
This article examines what potential effects the implementation of the payment system per "patient case" might have on the health service structure and providers' behaviour. Author analyzed the case of the pricing system of ambulatory services that was implemented in Poland in 2011. This system is based on the concept of ambulatory patient groups—the modification of diagnosis-related groups dedicated to the ambulatory health care. Improper design of grouping and pricing services—in particular, the lack of cost homogeneity and different level of profitability of different groups—may result in undesirable behaviours of providers, including, in particular, unjustified increasing or decreasing the number of services. The study shows that in recent years such undesirable phenomena occurred in Poland. In the case of most of the analyzed groups, the change in the price level resulted in the reaction of the providers that was significantly different from their behaviour in relation to other groups and/or behaviour in relation to tested variables in the period before the change in pricing.